EXPRESSIVE WRITING: IMPROVING OPTIMISM, PURPOSE, AND RESILIENCE WRITING AND GRATITUDE. (11th November 2018) - Wells, T; Albright, L; Keown, K; Tkatch, R; Duffy, M; Wu, L; Wicker, E
Abstract: Writing about traumatic, stressful or emotional events is associated with improvements in both physical and psychological health. There has been significant research on the benefits of expressive writing but few studies have addressed the needs of older adults specifically. The purpose of this study was to investigate whether or not expressive writing has an impact on sense of purpose, optimism, resilience or quality of life. A total of 153 participants were randomly assigned to either expressive writing (n=72) or gratitude journaling with expressive writing (n=81) Pre/post measures were collected over a two week period. Text or phone call reminders were provided to participants. Results of the post survey found that for those in gratitude and expressive writing; physical health, resilience, and optimism improved (p <.05). This intervention demonstrates that expressive writing may be beneficial for older adults and promote health and well-being.